Pengaruh Kualitas Pelayanan dan Promosi terhadap Keputusan Penggunaan Jasa Transportasi Online Grab pada Mahasiswa Fakultas Pertanian Universitas Methodist Indonesia - Yohana Kartika Siregar; Indawati Lestari (Lembaga Yasin AlSys, 2026)
Although the development of digital technology has brought significant changes to the transportation sector through the emergence of application-based services, the decision to use online transportation services remains influenced by various factors, particularly service quality and promotion. This study aims to analyze the effect of service quality and promotion on the decision to use Grab online transportation services among students of the Faculty of Agriculture, Universitas Methodist Indonesia. This study employed a quantitative approach using a survey method. The study population consisted of 643 students, with a sample of 247 respondents determined using the Slovin formula. Data were collected through the distribution of Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of the SPSS program. The results showed that service quality and promotion, both partially and simultaneously, had a positive and significant effect on the decision to use Grab online transportation services. These findings confirm that good service quality and attractive promotion can increase students’ decisions to use online transportation services. Thus, this study contributes to strengthening the study of consumer behavior in digital transportation services and provides practical implications for Grab in improving service quality and designing more effective promotional strategies to retain users.